New approaches to the study of nociception: identification and refinement of approaches for the use of Drosophila melanogaster in the drug discovery pipeline - Smith, Neave (2023)
Nociception is highly conserved between invertebrates and vertebrates. The bulk of basic biomedical research into pain and nociception relies on mammalian model systems with accompanying ethical, financial and time pressures. Thus, studies investigating the peripheral mechanisms of nociception in an invertebrate system where these concerns are reduced is highly desirable. Drosophila melanogaster utilise class IV dendritic arborization (C4da) neurons as polymodal nociceptors responsible for the detection of noxious mechanical, thermal, optical, and chemical stimuli. Transient receptor potential (TRP) channel mediated Ca2+ influx is crucial for the initiation of noxious signal transduction in both mammals and Drosophila, and the modulation of these responses by cAMP, following noxious stimulation, is common between both vertebrate and invertebrate sensory neurons. We selectively expressed a FRET (Foster resonance energy transfer)-based cAMP sensor and a genetically encoded Ca2+ indicator in the C4da nociceptive neurons. The spatiotemporal dynamics of signalling molecules underlying nociception have been monitored and quantified in Drosophila at single sensory neuron endings. We were able to induce a cAMP increase in the C4da nociceptive neurons with 50 uM Forskolin (FSK), an adenylyl cyclase activator (dynamic range ~6%). We report cinnamaldehyde (CA), a classic agonist of mammalian TRPA1, is able to activate the Drosophila TRPA1 homologues (dTRPA1 and/or Painless) expressed on these sensory neurons to induce a robust intracellular Ca2+ response (EC50 = 4.123 x 10-5 M). The CA-induced Ca2+ response observed is reproducible and can be pharmacologically inhibited by 20 uM AM0902. In mammalian sensory neurons there are temporal differences in the activation of distal and proximal terminals as well as the cell body. Within these cellular sub-compartments, it has been demonstrated that local processes, such as the regulation of expression key proteins involved in neuronal function take place. Importantly, we have demonstrated data can be obtained from different neuronal compartments of the C4da nociceptive neurons (distal dendrites, proximal dendrites, and soma). This model advocates the translational utility of Drosophila, demonstrating to the pain field that early proof of concept studies can be carried out in this non-mammalian system to reduce the numbers of successful candidate molecules being tested in rodents.